The true history of his captivity, 1557 - Staden, Hans, approximately 1525-approximately 1576 (Broadway travellers, 2005)
'The Broadway Travellers contains few more exciting stories than that of Staden.' Sunday Times'The present translation of his adventures among the Brazilian cannibals, with which the gruesome original woodcuts are included, now make Staden's story available to a larger public...'New StatesmanThe first part of the book is a straightforward account of the author's personal experiences. The second part is a detailed treatise on the customs of the Tupinambá, their polity, trade, religion, manufactures and warlike undertakings, and of the flora and fauna of the country. In.